Catalytic C - H amination with unactivated amines through copper(II) amides - Wiese, Stefan; Badiei, Yosra M.; Gephart, Raymond T.; Mossin, Susanne; Varonka, Matthew S.; Melzer, Marie M.; Meyer, Karsten; Cundari, Thomas R.; Warren, Timothy H. (Angewandte Chemie International Edition, 2010)
En route to catalysis: Two equivalents of the three-coordinate copper(II) amide [(Cl NN)Cu]-NHAd participate in stoichiometric C - H amination by a H-atom abstraction/radical capture sequence. This active species may be generated through a copper(II) tert-butoxide intermediate to allow for the unprecedented catalytic amination of sp -C - H bonds with unactivated alkylamines. This method greatly expands the range of amines for catalytic C - H amination since most protocols require N-based electron-withdrawing groups. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.